LINC00963 promotes the malignancy and metastasis of lung adenocarcinoma by stabilizing Zeb1 and exosomes-induced M2 macrophage polarization - Ronghang Hu; Baobin Xu; Jiajun Ma; Linfeng Li; Liming Zhang; Li Wang; Jiebo Zhu; Tao Guo; Heng Zhang; Shaoqiang Wang (BMC, 2023)
Abstract Background Long intergenic non-coding RNA 00963 (LINC00963) is an oncogenic lncRNA in human cancers. However, little is known on how it impacts the pathogenesis of lung adenocarcinoma (LUAD). Methods Biological effects on proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) were examined by CCK-8, colony formation, EdU incorporation, transwell, and immunofluorescence assays, respectively. Macrophage polarization was evaluated by flow cytometry. Ubiquitination of Zeb1 was examined by co-immunoprecipitation. The location of LINC00963 in LUAD tissues and cell lines was tested by FISH assay. The LINC00963/HNRNPA2B1/Siah1 mRNA complex interaction was verified using RNA pull-down and immunoprecipitation assays. The exact roles of LINC00963 were further validated in metastasis and xenograft models. Results Higher LINC00963 expression in LUAD patients positively correlated with shorter overall survival, higher stages, and metastasis. LINC00963 mainly localized in the cytoplasm and aggravated malignant phenotypes of LUAD cells in vitro and metastasis in vivo. Mechanistically, LINC00963 directly interacted HNRNPA2B1 protein to trigger the degradation of Siah1 mRNA, which inhibited the ubiquitination and degradation of Zeb1. Moreover, exosomal LINC00963 derived from LUAD cells induced M2 macrophage polarization and promoted LUAD growth and metastasis. Conclusion By stabilizing Zeb1 in cancer cells and delivering exosomes to induce M2 macrophage polarization, LINC00963 promoted the malignancy and metastasis of LUAD. Targeting LINC00963 may become a valuable therapeutic target for LUAD.